Prevalência de aleitamento materno e os fatores associados ao desmame precoce - Kamiya, Elisabete (2012)
OBJECTIVE. To assess factors associated with breastfeeding in children up to 6 months attending primary healthcare units in Campo Grande-MS and the introduction of other milks and foods. METHODS. Observational cross-sectional research conducted by the application of an instrument of data collection provided by mothers. RESULTS. The prevalence of exclusive breastfeeding up to 6 months among 241 children was 51.9%, and prevalence of breastfeeding was 94.2%. In comparing exclusive and non-exclusive breastfeeding, there was no significant difference in the socioeconomic conditions of mothers. Difference was significant, though, in the use of tea and pacifier and in the mothers opinion on the quantity of their milk. Of the infants who were exclusively breastfed, 28% had previous contact with the bottle or pacifier and 20%, water or tea, or both. In the case of nonexclusive breastfeeding, 71.6% had already used a pacifier/bottle and 92.2%, water or tea. Regarding the type of milk consumed, 77.6% of babies were exclusively breastfed, 16.6% consumed milk and cow's milk, and 5.8%, only cow's milk. Among those who drank cow's milk (22.4%) this introduction occurred mainly in the first month (61.2%). Early weaning has occurred because, according to the mothers, the production of milk was insufficient (42.1%); the need to work or study stood for 21% of justifications. The introduction of complementary foods had already occurred to 4.1%. CONCLUSIONS. There was improvement in the prevalence of exclusive breastfeeding, but variables such as use of pacifier, fluid offer and lack of confidence of the mother are still challenges to public health. Of the 241 children, 22.4% drank cow's milk and 4.1% had introduced complementary foods.